Fiqh Teachers’ Strategy in Implementing the Practice of Prayer at MTs Babussalam Tebo Jambi - Guspita Wati (Universitas Muhammadiyah Enrekang, 2023)
This study aimed to identify the strategies used by fiqh teachers in activating the practice of congregational prayers for MTs Babussalam Tebo Jambi students, then identify the supporting and inhibiting factors and investigate how these problems can be overcome with various solutions. Normative theological, pedagogical, and psychological are the approaches used in this research. The primary data sources come from observations and interviews with teachers and students. In comparison, secondary data comes from library data and school documents. Data collection techniques in this study used interviews, observation, and documentation. This study found that fiqh teachers used various strategies to implement congregational prayer practices at MTs Babussalam Tebo Jambi, such as habituation strategies, motivation, example, discipline enforcement, and punishment application. The supporting factors are a religious school environment, teacher support and motivation, school residents who are predominantly Muslim, and the availability of facilities and infrastructure. In comparison, the inhibiting factors are students' need for self-awareness about the obligation to pray, the lack of supporting infrastructure such as mukena, the lack of awareness of teachers controlling students, and the lack of attention from parents. Help students perform congregational prayers. Besides that, it also schedules teachers to guide and supervise student participants and prepare special times for congregational prayers that have been determined in the daily prayer schedule.